Employment precarization in a Public Hospital in Sergipe: a case study with nursing professional - Tereza Cecília Costa do Nascimento; Marley Rosana Melo de Araújo; Saulo Pereira de Almeida (Revista de Ciências da Administração : RCA, 2018)
This study investigated the perception of precarious employment in a public hospital in the State of Sergipe. The Occupational Precariousness Inventory (IPREL) was applied to 279 nursing professionals and, after Main Axes Factorial Analysis, Promax Rotation, 2 factors were extracted (Occupational Hygiene and Justice: α = 0,87, Work Relations: α = 0,67) explaining 19.09% of the data variance. Nursing workers rarely experience adequate and safe working conditions and a perception of fairness in the relationships established at work (M = 1,5, SD = 0,52), although they show a reasonable occurrence, by the employers organization, of people management practices interested in professional recognition, participation in decision-making, and the observance of labor remuneration obligations (M = 2,0, DP = 0,51). The results point to a more critical framework regarding work material conditions and equity relations, signaling the need for corrective improvements.